2014
DOI: 10.1002/cam4.304
|View full text |Cite
|
Sign up to set email alerts
|

The association between lifetime smoking exposure and breast cancer mortality – results from a Norwegian cohort

Abstract: Several recent cohort studies have found an association between smoking and breast cancer, but the association between lifetime smoking exposure and breast cancer mortality is less well described. We examined whether smoking before breast cancer diagnosis is a predictor of breast cancer mortality in a large cohort with more than 4.1 million years of follow-up, with a special focus on women who initiated smoking before first childbirth. Information on smoking status was collected before breast cancer diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(95 reference statements)
0
4
1
Order By: Relevance
“…Our results do not conclusively confirm associations with other known lifestyle-related risk factors [3,4], such as tobacco use [39][40][41][42][43] and alcohol consumption [6,[44][45][46][47]; this could be due to the limitations of the study, which are outlined later in this section.…”
Section: Discussioncontrasting
confidence: 73%
“…Our results do not conclusively confirm associations with other known lifestyle-related risk factors [3,4], such as tobacco use [39][40][41][42][43] and alcohol consumption [6,[44][45][46][47]; this could be due to the limitations of the study, which are outlined later in this section.…”
Section: Discussioncontrasting
confidence: 73%
“…However, results from several recent cohort studies, not included in the above-listed expert reports, on smoking and breast cancer incidence ( Bjerkaas et al , 2013 ; Gaudet et al , 2013 ; Rosenberg et al , 2013 ; Dossus et al , 2014 ; Nyante et al , 2014 ; Catsburg et al , 2015 ; Gram et al , 2015 ) and mortality ( Bjerkaas et al , 2014 ; Carter et al , 2015 ) suggest that the burden of smoking on society is underestimated.…”
mentioning
confidence: 99%
“…While 10% of females who continued to smoke after diagnosis, had a 1.7-fold higher risk of dying from breast cancer (HR=1.72; 95% CI: 1.13-2.60), as compared with nonsmoking. According to Bjerkaas et al, (43) several large prospective cohort studies have found that smoking can cause breast cancer, especially in females who smoke for an extended period of time, those who smoke a great number of cigarettes per day and those who smoke before delivering their first child. Their research results showed that the mortality from breast cancer may indeed be low, but increases significantly for active smoking (current) and former smoking (HR=1.15; 95% CI: 1.01-1.32 and HR=1.15; 95% CI: 1.02-1.30, respectively), as compared with nonsmoking.…”
Section: Discussionmentioning
confidence: 99%